Health Solidarity in Practice - Dominika Krištofičová (Slovak Yearbook of European Union Law, 2026)
The pharmaceutical sector highlights the tension between Member State responsibility for healthcare and the growing role of EU regulation. This paper examines the EU´s competences in the pharmaceutical sector de lege lata, focusing on their legal basis and the existing regulatory instruments. It examines relevant provisions of the Treaties and their implications for the role of solidarity in legal basis to adopt regulatory measures in the pharmaceutical sector. The paper further analyses the legal framework governing medicinal products in the EU and explores how the principle of solidarity is reflected in the design and functioning of these regulatory principles. By examining the legal basis and regulatory tools of EU pharmaceutical law, the article aims to assess how solidarity is embedded within the current competence framework of the EU law.